2000
DOI: 10.1093/ptr/10.4.421
|View full text |Cite
|
Sign up to set email alerts
|

Patient Attachment Orientation and the Early Working Alliance-A Study of Patient and Therapist Reports of Alliance Quality and Ruptures

Abstract: This study investigated the relationship between attachment orientation in adult patients and the early therapeutic alliance. Attachment was measured by self-report following the first session of therapy. The alliance was studied using patient and therapist ratings of its quality and reports of ruptures following early sessions. The sample comprised 30 clinical psychology outpatients treated by 11 experienced therapists. Correlation and multiple regression statistics provided partial support for the hypothesiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
152
0
13

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(180 citation statements)
references
References 27 publications
15
152
0
13
Order By: Relevance
“…Both of these findings are consistent with previous studies. Several studies have found that secure attachment style in therapists was positively associated with therapeutic alliance and therapy outcome (Meyer, Pilkonis, Projetti, Heape, & Egan, 2001;Bartholomew, 1997;Dozier, 1990;Dozier, Lomax, & Tyrell, 1996;Satterfeld & Lyddon, 1998;Eames & Roth, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Both of these findings are consistent with previous studies. Several studies have found that secure attachment style in therapists was positively associated with therapeutic alliance and therapy outcome (Meyer, Pilkonis, Projetti, Heape, & Egan, 2001;Bartholomew, 1997;Dozier, 1990;Dozier, Lomax, & Tyrell, 1996;Satterfeld & Lyddon, 1998;Eames & Roth, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…This has received some empirical support in the psychotherapeutic literature (Dolan et al, 1993;Eames & Roth, 2000). In a study of 30 clinical psychology out-patients, Eames & Roth found that patients classified as fearful using Bartholomew's classification (Bartholomew & Horowitz, 1991), i.e.…”
Section: Patient Attachment the Working Alliance And How Patients Mamentioning
confidence: 97%
“…In addition to these intrapsychic factors, patient interpersonal characteristics have been shown to relate to the alliance. Specifically, patient attachment style has been associated with the therapeutic alliance in several studies such that patients with secure attachment styles were more likely to have favorable therapeutic relationships, while those with fearful, preoccupied, anxious, or dismissive attachments had more difficulty establishing or maintaining a good alliance (e.g., Dolan, Arnkoff & Glass, 1993;Eames & Roth, 2000;Rubino, Barker, Roth, & Fearson, 2000).…”
Section: Correlates Of the Therapeutic Alliancementioning
confidence: 99%